Source analysis of the N2 in a cued Go/NoGo task - Bekker, Evelijne M.; Kenemans, J. Leon; Verbaten, Marinus N. (Brain research. Cognitive brain research, 2005)
Previous source analyses of event-related potential (ERP) data elicited in Go/NoGo tasks have suggested that the anterior cingulate cortex (ACC) plays an important role in response inhibition. So far, however, source models were derived for the difference wave Go stimulus minus NoGo stimulus. This difference wave is confounded with motor- and attention-related activity. To avoid these confounds, we alternatively derived source models for NoGo stimuli only. The problem of the NoGo-N2 being superimposed on a positive deflection was addressed in two ways. First, a baseline correction was applied using the time points just preceding and succeeding the NoGo-N2. Second, a separate source model was derived at the maximum amplitude of this positive deflection. Subjects were presented with a cued version of the continuous performance task (CPT; ABX). In a second study, the probability of the Go stimulus was gradually increased to heighten subjects' tendency to respond and, as a consequence, to enhance the amplitude of the NoGo-N2. The source models of the NoGo-N2 consistently indicated bilateral dipole pairs in medial frontal regions. This is in accordance with a generator in the anterior cingulate cortex.